Kepemilikan Hak Atas Tanah dalam Perkawinan Campuran - I Gede Wardana Oka Sastra Wiguna; I Nyoman Putu Budiartha; I Putu Gede Seputra (Jurnal Konstruksi Hukum, 2020)
The study of this research is a review of the ownership of land rights for husbands / wives as a result of the existence of mixed marriages, currently mixed marriages exist in various circles of Indonesian society, the cause of this legal incident is the result of the fast and easy development of the times, and is supported by international relations that continue to increase. With the occurrence of many mixed marriages in Indonesia, legal protection in mixed marriages should be accommodated properly in the legislation in Indonesia. The purpose of this research is to understand the arrangement of ownership of land rights according to Law Number 5 of 1960 concerning agrarian principles and to know the status of ownership of land rights that can be owned in mixed marriages. Researchers use normative techniques, namely normative legal research methods or library law research methods, which are methods or methods used in legal research conducted by examining existing library materials. This research illustrates that the ownership of land rights according to Law Number 5 of 1960 concerning Basic Basic Agrarian Regulations in general, land rights can be in the form of property rights, land use rights, land use rights, and finally use rights which are between one and one rights. Other rights have different meanings in terms of limitations on legal subjects of ownership and limitations on the duration of ownership. The status of ownership of land rights that can be owned in mixed marriages is attached to people who have Indonesian citizenship and in mixed marriages the problems of ownership of the rights over can be resolved by a marriage agreement made between the parties.